Exploring the Role of North Sulawesi’s Local Culture in Shaping National Identity and Character Education Among Students - Lonto, Apeles Lexi; Winoto, Darmawan Edi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Using the literature review method, this study investigated how the culture of North Sulawesi functioned as a source of national identity and a foundation for character education in students. According to research conducted on a number of indexed scholarly journals and articles, local values such as mapalus, karai, gratitude, and multiculturalism shaped students’ character to be national-minded, tolerant, and moral. Emphasis was placed on efforts to integrate local culture into the secondary school curriculum as a way to enhance the identity and morals of the younger generation. In this regard, previous research results showed that local culture not only represented symbolism; when used as a pedagogical tool, it also helped to cultivate character. The findings indicated that local culture was not just a symbol of identity but also an effective pedagogical instrument in shaping national character.